2007
DOI: 10.1007/s10800-007-9470-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of tin and antimony in 1-ethyl- 3-methylimidazolium tetrafluoroborate ionic liquid

Abstract: The electrodepositions of Sn(II) and Sb (III) were studied in the [EMIm]BF 4 ionic liquid at ambient temperature. Linear sweep voltammetry (LSV) results indicated that the reductions of Sn(II) and Sb(III) on Pt electrode are electrochemically irreversible. The diffusion coefficients of Sn(II) and Sb(III) in the ionic liquid electrolyte were determined in terms of the LSV data. Tin and antimony ions form simpler Sn(II) chlorocomplex species and higher Sb(III) chlorocomplexes, respectively present in the ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
1
29
1
Order By: Relevance
“…It can be suggested that the complexation between the Tin(II) with trifluoromethylsulfonate and trifluoromethylsulfonyl imide, which is larger than the chloride ion and the tetrafluoroborate ion, has increased the radius of the Tin(II) species in solution. This contributes to the lower diffusion coefficient compared with the chloride and tetrafluoroborate based ionic liquids from the works of Hussey and Xe [6] and Yang et al [7] It can also be said that the diffusion coefficient from this work using trifluoromethylsulfonate ionic liquid has a greater value compared with the trifluoromethylsulfonyl imide, [8] which is in accordance with larger dynamic radius of the trifluoromethylsulfonyl imide ionic liquid compared with the trifluoromethylsulfonate ionic liquid.…”
Section: Diffusion Coefficientssupporting
confidence: 55%
See 2 more Smart Citations
“…It can be suggested that the complexation between the Tin(II) with trifluoromethylsulfonate and trifluoromethylsulfonyl imide, which is larger than the chloride ion and the tetrafluoroborate ion, has increased the radius of the Tin(II) species in solution. This contributes to the lower diffusion coefficient compared with the chloride and tetrafluoroborate based ionic liquids from the works of Hussey and Xe [6] and Yang et al [7] It can also be said that the diffusion coefficient from this work using trifluoromethylsulfonate ionic liquid has a greater value compared with the trifluoromethylsulfonyl imide, [8] which is in accordance with larger dynamic radius of the trifluoromethylsulfonyl imide ionic liquid compared with the trifluoromethylsulfonate ionic liquid.…”
Section: Diffusion Coefficientssupporting
confidence: 55%
“…Yang et al [7] used tetrafluoroborate, BF 4 À -based ionic liquid, where the diffusion coefficient was higher than calculated from the chloroaluminate ionic liquid by Hussey and Xe. [6] It can observed that the smaller Tin(II) tetrafluoroborate species will contribute to a slightly higher diffusion coefficient value for the Tin(II) species.…”
Section: Diffusion Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of current maxima in the forward and reverse sweep varied with scan rate, which shows a quasi reversible or irreversible process for Sn. 28,29 The diffusion coefficient of Cu was determined using the Randles-Sevčik equation for reversible couples using the peak appearing at (0?45 V/0?35 V). According to Randles-Sevčik 30…”
Section: Resultsmentioning
confidence: 99%
“…The study of the effect of various functional cations/anions on ILs has been a hot topic [4][5][6][7][8][9]. Moreover, the dialkylimidazolium-based ILs with thiocyanate (SCN) anion have attracted significant attention because of their low dynamic viscosities [10,11].…”
Section: Introductionmentioning
confidence: 99%